Near-field sea-level variability in northwest Europe and ice sheet stability during the last interglacial: - Long, A.J.; Barlow, N.L.M.; Busschers, F.S.; Cohen, K.M.; Gehrels, W.R.; Wake, L.M. (Elsevier Ltd, 2015)
Global sea level during the Last Interglacial (LIG, Marine Isotope Sub-stage 5e) peaked between c. 5.5 and 9 m above present, implying significant melt from Greenland and Antarctica. Relative sea level (RSL) observations from several far- and intermediate-field sites suggest abrupt fluctuations or jumps in RSL during the LIG highstand that require one or more episodes of ice-sheet collapse and regrowth. Such events should be manifest as unique sea-level fingerprints, recorded in far-, intermediate- and near-field sites depending on the source(s) of ice-mass change involved. To date, though, no coherent evidence of such fluctuations has been reported from near-field RSL studies in northwest Europe. This is an important problem because RSL fluctuations during the LIG are portrayed as warning signs for how polar ice sheets may behave in a future, warmer than present, world. Here we review the evidence for RSL change during the LIG using stratigraphic data from the best resolved highstand records that exist in the near-field of northwest Europe, from a range of settings that include lagoonal, shallow marine, tidal flat, salt marsh and brackish-water fluviatile environments. Consideration of previously published stratigraphic records from two sites in the Eemian coastal-marine embayment that existed in the central Netherlands, yields no clear indications for abrupt RSL change during the attainment of the near-field highstand. Nor do we find any such indications common to other records from countries bordering the North Sea, the Baltic Sea and the White Sea. Two modelling experiments that explore the global signal of hypothetical sea-level oscillations caused by partial collapse and regrowth of either the Greenland or Antarctic LIG ice-sheet, show that the North Sea region is relatively insensitive to mass changes sourced from Greenland but should clearly register events with an Antarctic origin, especially those that occur late in the LIG. The lack of evidence for abrupt sea-level fluctuations at this time in northwest Europe concurs with a lack of clear near-field evidence for ice sheet collapse. © 2015 Elsevier Ltd.